Assessing Customer Trust, Satisfaction, and Loyalty in the Malaysian Ice Cream and Milk Tea Industry - Hala Najwan; Oh ZI Jian; Wen Kai Goh; Yong Teng Foo; Fatimah Az Zahraa` Azali; Xi Gao; Arya Tripathi; Daisy Mui Hung Kee (Journal of The Community Development in Asia, 2024)
This study investigates customer satisfaction, trust, and loyalty within Malaysia's ice cream and milk tea industry, focusing on Mixue Ice Cream Tea. While previous research has predominantly examined how factors such as taste, perceived price, and service quality impact customer satisfaction, this study aims to bridge the gap by exploring the transition from customer loyalty to brand loyalty and its subsequent effect on brand competitiveness. Utilizing a quantitative approach, online surveys were administered to milk tea consumers across Malaysia. The analysis reveals that customer satisfaction and customer loyalty have a positive association, supporting Hypothesis H1, while customer trust significantly influences customer loyalty, confirming Hypothesis H2. However, the analysis rejects Hypotheses H4 and H5, indicating no substantial positive association between customer satisfaction and trust with brand loyalty. Notably, customer loyalty shows a strong positive relationship with brand loyalty, thus supporting Hypothesis H3. These findings contribute to the existing literature by detailing how customer satisfaction and trust evolve into strong brand loyalty and provide strategic recommendations to enhance Mixue Ice Cream Tea's competitiveness in the FB sector